Relevansi Konsep Pemikiran Ibnu Khaldun dan Projek Penguatan Profil Pelajar Pancasila dalam Menanamkan Karakter Anak Usia Dini - Liana, Disti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the concept of Ibn Khaldun's Thought and Its Relevance to the Pancasila Student Profile Strengthening Project in Instilling Good Character in Early Childhood. The research method uses qualitative descriptive with the type or nature of library research, the technique used is that the researcher collects data related to the research in the form of books, manuscripts, articles, previous research reports, newspapers both online and offline, and so on. Based on the results of the study, it can be concluded that the relevance of the concept of Ibn Khaldun's thought and the Pancasila Profile Strengthening Project in the Foundation Phase is that he considers character education to be an important foundation for the development of sustainable civilization. Character education must include the development of moral values, good character, critical thinking skills, and responsible leadership. In realizing good character education, all elements (Educational Institutions, families, and student environments) must be actively involved. Keywords: Ibn Khaldun's Thought, Pancasila Student Profile Strengthening Project (P5), Early Childhood Character